2016
DOI: 10.1155/2016/1062878
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biological Assessment of Zinc Doped Hydroxyapatite Nanoparticles

Abstract: The aim of the current research work was to study the physicochemical and biological properties of synthesized zinc doped hydroxyapatite (ZnHAp) nanoparticles with Zn concentrations Zn = 0 (HAp), Zn = 0.07 (7ZnHAp), and Zn = 0.1 (10ZnHAp) for potential use in biological applications. The morphology, size, compositions, and incorporation of zinc into hydroxyapatite were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier Transform Infrared Spectroscopy (FTIR), Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 41 publications
8
59
1
Order By: Relevance
“…The crystallite size of the prepared HAp obtained from Scherrer’s equation was 83.5 ± 1 nm. Similar results were also obtained in our previous studies [ 61 , 62 ]. According to A. Bigi et al [ 62 ], the values of the parameters of the sides “a” and “c” are influenced both by the synthesis method, and the pH at which synthesis was achieved.…”
Section: Resultssupporting
confidence: 93%
“…The crystallite size of the prepared HAp obtained from Scherrer’s equation was 83.5 ± 1 nm. Similar results were also obtained in our previous studies [ 61 , 62 ]. According to A. Bigi et al [ 62 ], the values of the parameters of the sides “a” and “c” are influenced both by the synthesis method, and the pH at which synthesis was achieved.…”
Section: Resultssupporting
confidence: 93%
“…Certain studies have examined the effect of other thin layers on C. albicans [ 14 ]. Recent research regarding the effect of antimicrobial activity of Zn:HAp nanoparticles is available [ 25 , 26 ]. In recent studies on textural, structural and biological evaluation of hydroxyapatite doped with zinc at low concentrations, Predoi et al [ 25 ] assessed the effect of Zn:HAp on cell viability on prokaryote and eukaryote cells.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the cytotoxic effects were intense in the case of hepatic cells. Furthermore, the studies on structural and biological assessment of zinc doped hydroxyapatite nanoparticles conducted by Popa et al [ 26 ] concluded that that “Zn doping at the tested concentrations did not induce a specific prokaryote or eukaryote toxicity in HAp compounds” and clearly showed that the activity of Zn:HAp nanoparticles against HepG2 cells was meaningfully dependent on the particle size. Another study on flower-shaped ZnO nanoparticles synthesized by a novel approach at near-room temperatures with antibacterial and antifungal properties conducted by Khan et al [ 35 ] showed that the antimicrobial effects can be influenced by the shape of nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal ions such as Ag + , Zn 2+ , and Cu 2+ can be transported by HAp through ionic substitution. The anterior results showed that the Ag + and Zn 2+ affect the development of microorganisms . In contrast, in the precedent studies conducted on bacterial resistance to silver in wound care revealed that the Ag + show oligodynamic effect with minimum development of resistant microorganisms.…”
Section: Resultsmentioning
confidence: 89%